Analysis of Klavdii Semyonovich Nemeshaev’s activities as the Minister of Railways of the Russian Empire - Олег Стрелко; Олег Пилипчук (History of science and technology, 2021)
The article continues the series of publications devoted to the assessment of activities of the heads of the Ministry of Railways of the Russian Empire. In this article, the authors attempt to systematize and analyze historical data on the activities of Klavdii Semyonovich Nemeshaev as the Minister of Railways of the Russian Empire. There are numerous biographical studies devoted to K. S. Nemeshaev, but little is known about his activities as a minister, and to date the data are scattered and not systematized. The analysis of archival materials, scientific publications, memoirs of Nemeshaev's contemporaries and colleagues allowed us to conduct a detailed assessment of his activities and ministerial policy. It has been found that despite his short term of office, Nemeshaev's consistent policy and extensive managerial experience allowed him to carry out two significant reforms in a short time. The first one involved redistribution of the state-owned railway lines between separate local administrations and merging them into larger groups, which was important in terms of improving their operations and facilitating the cost efficiency, as well as speeding up freight traffic. In opinion of the authors of this article, another important achievement of Nemeshaev as the Minister of Railways was the establishment in 1906 of the central, local and district committees regulating mass transportation of goods. This was the first centralized measure aimed at managing the rolling stock. Nemeshaev's extensive managerial experience, high erudition and energy also led to prominent outcomes in some other areas of the Ministry operation. Attempts were made to create syndicates of shipowners in river transport. Modernization of river and sea vessels was carried out. Works on projects for the development of the Northern Sea Route has begun. The article also assesses the development and construction of railway network in the Russian Empire during Nemeshaev's office, in particular, of the Amur Line and Moscow Encircle Railway, as well ...